Might salivary Lysozyme be an indicator of prolonged intense training load in athletes? A preliminary study in adolescent male gymnasts - Vána, P.; Juríková, J.; Bernaciková, M.; Ševcík, R.; Žákovská, A.; Hedbávný, P. (Studia Sportiva, 2020)
Lysozyme is one of the salivary antimicrobial proteins (AMP) which act as a defence at the mucosal surface. While in adult athletes, a decrease in salivary lysozyme (SLys) levels has been reported after prolonged intense training, to our knowledge, no studies have been conducted to study the relationship between SLys levels and long-term physical activity in children or teenagers.